Sustainability indicators of a naturally ventilated photovoltaic façade system. (1st September 2020) - Garraín, Daniel; Herrera, Israel; Rodríguez-Serrano, Irene; Lechón, Yolanda; Hepbasli, Arif; Araz, Mustafa; Biyik, Emrah; Yao, Rumming; Shahrestani, Mehdi; Essah, Emmanuel; Shao, Li; Rico, Elena; et al.
Abstract: Building Integrated Photovoltaic (BIPV) systems have been increasingly used as a means to generate electricity on-site, and their diffusion will increase in the near future. The objective of this article is to carry out a sustainability assessment of a BIPV system installed in Turkey regarding the three pillars: environmental, economic and social potential impact, in order to develop different indicators. For the socioeconomic analysis, a Multiregional Input-Output (MRIO) method was used to estimate production of goods and services, value added creation and employment opportunities. For the environmental evaluation, an Environmental Footprint (EF) analysis was performed. The levelized electricity costs and the greenhouse gas emissions abatement costs were also calculated. Results showed that the socioeconomic effects are relevant, although only a 23% of these effects remain in Turkey. The environmental profile is also good in terms of climate change impacts, showing substantial reductions in greenhouse gas emissions compared to fossil fuel alternatives for electricity generation. Regarding the life cycle stages of the technology, the highest environmental impacts are produced in the PV manufacturing processes. The electricity produced is still more costly than fossil-based technologies and in the highest range of PV technologies, but greenhouse gases abatement costs are not so high when compared to other references. Highlights: The socioeconomic effects of the deployment of a BIPV system are relevant: a high multiplier effect (23% remain in Turkey). Substantial reductions in GHG emissions compared to fossil fuel alternatives for electricity generation can be obtained. The highest environmental impacts are due to the PV manufacturing processes. The electricity produced is still more costly than fossil-based technologies and in the highest range of PV technologies. GHG abatement costs are not so high when compared to other references.